![image](https://tex.z-dn.net/?f=++log_%7B+%5Cfrac%7B1%7D%7B2%7D%7D%287-3x%29%3E%3D-2+)
=-2 " alt=" log_{ \frac{1}{2}}(7-3x)>=-2 " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+log_%7B+%5Cfrac%7B1%7D%7B2%7D%7D%287-3x%29%3E%3D-2)
=-2" alt=" log_{ \frac{1}{2}}(7-3x)>=-2" align="absmiddle" class="latex-formula"> =>
![image](https://tex.z-dn.net/?f=7-3x%3E%3D%28+%5Cfrac%7B1%7D%7B2%7D%29%5E%7B-2%7D)
=( \frac{1}{2})^{-2}" alt="7-3x>=( \frac{1}{2})^{-2}" align="absmiddle" class="latex-formula"> => 7-3x>=4 => 3x=<3 => x=<1. Но, так как основание >0 => 7-3x>0 => 3x<7 => x<7/3<br>Прошу пока повременить. Я кажется поспешил...